2023
DOI: 10.1186/s12913-022-09015-w
|View full text |Cite
|
Sign up to set email alerts
|

Solutions for improved hospital-wide patient flows – a qualitative interview study of leading healthcare providers

Abstract: Background Hospital productivity is of great importance for patients and public health to achieve better availability and health outcomes. Previous research demonstrates that improvements can be reached by directing more attention to the flow of patients. There is a significant body of literature on how to improve patient flows, but these research projects rarely encompass complete hospitals. Therefore, through interviews with senior managers at the world’s leading hospitals, this study aims to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…[36] Improving patient access can be achieved by standardising communication between departments in referral pathways and strategically adjusting capacity distribution based on demand patterns. [37] Additionally, combining bed pools within the facility and externally produces better performance.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Improving patient access can be achieved by standardising communication between departments in referral pathways and strategically adjusting capacity distribution based on demand patterns. [37] Additionally, combining bed pools within the facility and externally produces better performance.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights to troubleshoot severe inadequacy of service by involved the senior manager. This effort is beneficial because the senior manager has more experience and more influence to the hospital service process [22]. The significance of effective internal processes and a skilled workforce in driving organizational performance in the healthcare sector [14,15].…”
Section: Path Analysismentioning
confidence: 99%
“…Studies have shown that addressing patient flow issues can have several benefits, including reduced length of stay (LOS) and faster discharge process [ 1 , 2 , 20 , 21 ]. Improving patient flow is essential for enhancing medical quality, safety, and patient satisfaction while also reducing input and facilitating throughput and output from hospitals and EDs [ 3 , 8 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in demographics, the prevalence of multimorbidity, the ongoing challenges posed by the COVID-19 pandemic, and persistent shortages in healthcare staffing have significantly increased the demand for healthcare services. [1][2][3]. Most hospitals face a mismatch between supply and demand, resulting in delays, staffing gaps, and inefficient hospital ward utilisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation